Dysregulated Peripheral Invariant Natural Killer T Cells in Plaque Psoriasis Patients - Hu, Yifan; Chen, Youdong; Chen, Zeyu; Zhang, Xilin; Guo, ChunYuan; Yu, ZengYang; Xu, Peng; Sun, Lei; Zhou, Xue; Gong, Yu; Yu, Qian; Shi, Yuling (Frontiers in Cell and Developmental Biology, 2022)
Background: Psoriasis is a common immune-mediated skin disease that involves T-cell-mediated immunity. Invariant natural killer T (iNKT) cells are a unique lymphocyte subpopulation that share properties and express surface markers of both NK cells and T cells. Previous reports indicate that iNKT cells regulate the development of various inflammatory diseases. IL-17 is a key cytokine in the pathogenesis of psoriasis and a key therapeutic target. Secukinumab is a fully human IgG1κ antibody that targets IL-17A, thereby antagonizing the biological effects of IL-17. Objective: To explore the expression of iNKT cells in psoriasis patients and the effect of secukinumab on them. Methods: We examined the frequencies of iNKT cells, Tregs, naïve and memory CD4+and CD8+T cells in the PBMCs as well as their cytokine production in a cohort of 40 patients with moderate-to-severe plaque psoriasis and 40 gender- and age-matched healthy controls. We further collected peripheral blood of another 15 moderate-to-severe plaque psoriasis patients who were treated with secukinumab and evaluated the proportion of iNKT cells in the PBMCs at baseline and week 12. Results: The frequencies of conventional CD4+ T cells, CD8+ T cells, and Tregs in the PBMCs were comparable between psoriasis patients and healthy controls, but the frequencies of Th17 cells, Tc1 cells and Tc17 cells were increased in psoriasis patients. The frequency of peripheral iNKT cells and CD69+ iNKT cells was significantly decreased in psoriasis patients. Both iNKT2 cells and iNKT17 cells were increased in psoriasis patients, but the ratio of iNKT2 cells vs iNKT17 cells was significantly reduced in psoriasis patients. After receiving secukinumab, the proportion of iNKT cells in the PBMCs of patients was increased, while the proportion of iNKT17 cells was decreased. Conclusion: Dysregulated iNKT cells may be involved in the pathogenesis of psoriasis and secukinumab may play a regulatory role on iNKT cells.